Work-life balance - Xu, Mengyi; Kelliher, Clare (Routledge, 2024)
This chapter provides an overview of work-life balance (WLB), concerned with the relationship between an individual’s work and non-work lives. It first introduces and discusses the complexity of work-life balance as a concept and then examines how national, organisational, and temporal contexts may shape how it is understood and enacted. In addition, the chapter critically reviews formal and informal approaches to managing work-life balance for both employees and the organisation. While interest in work-life balance has been widespread and received much attention in academia, institutional and organisational agendas, and public discourse, to date, there has been limited attention given to its meaning and implementation in non-western contexts. This chapter addresses this gap by including a case study in the Chinese context. Using ‘Beyond Management Consulting Ltd’., as a case study, the opportunities for and challenges of managing work-life balance are discussed in the Chinese context. The chapter concludes by emphasising the complexity and dynamic nature of the notion of work-life balance and the necessity of considering inclusivity in how work-life balance is managed.